2021
DOI: 10.1017/s1366728921000973
|View full text |Cite
|
Sign up to set email alerts
|

Language control in regional dialect speakers – monolingual by name, bilingual by nature?

Abstract: While research on bilingual language processing is sensitive to different usage contexts, monolinguals are still often treated as a homogeneous control group, despite frequently using multiple varieties that may require engagement of control mechanisms during lexical access. Adapting a language-switching task for speakers of (Scottish) Standard English and Orcadian Scots, we demonstrate switch cost asymmetries with longer naming latencies when switching back into Orcadian. This pattern, which is reminiscent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 64 publications
1
13
1
Order By: Relevance
“…Security is a relative concept, and the design of AC technology depends on the particularity of the protected environment [5][6].…”
Section: The Principle Of Acmentioning
confidence: 99%
“…Security is a relative concept, and the design of AC technology depends on the particularity of the protected environment [5][6].…”
Section: The Principle Of Acmentioning
confidence: 99%
“…Previous research has indicated that when bidialectals (i.e., speakers of a regional dialect that are also fluent in a standard language variety) produce language, both the standard language and dialect are activated (e.g., [ 1 , 2 ]), which is assumed to lead to competition among both language varieties. Similar to bilinguals (for reviews, see [ 3 , 4 ]), a language control process is assumed to be implemented to deal with the competition between language varieties in bidialectals [ 1 2 , 5 , 6 ]. Some studies have suggested that the language control process implemented by bidialectal speakers of closely related language varieties is similar to the bilingual language control process [ 1 , 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to bilinguals (for reviews, see [ 3 , 4 ]), a language control process is assumed to be implemented to deal with the competition between language varieties in bidialectals [ 1 2 , 5 , 6 ]. Some studies have suggested that the language control process implemented by bidialectal speakers of closely related language varieties is similar to the bilingual language control process [ 1 , 2 , 5 ]. In the current study, we set out to further investigate the language control process implemented by bidialectals and its relation to the bilingual language control process by letting bidialectals perform in a voluntary language switching paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study (Kirk et al, 2022), bi‐dialectal speakers of Orcadian Scots (a regional dialect used in Orkney, Scotland) and Scottish Standard English have displayed switch cost asymmetries in language‐switching tasks. Longer response time was observed when bi‐dialectal participants switch from Scottish Standard English into Orcadian (as compared to the reverse), and this pattern of results highly resembles that of unbalanced bilinguals.…”
Section: Introductionmentioning
confidence: 99%